Derivation of Some Identities and Applications: Annual Meeting in Mathematics 2023 - Chaichana, Tuangrat; Laohakosol, Vichian; Meesa, Rattiya (Thai Journal of Mathematics, 2024)
Certain identities based on recurrently published results about explicit solutions of general second-order linear recurrences are proved and are used to derive explicit solutions of four well-known recurrence relations with polynomial coefficients.